2011
DOI: 10.1051/alr/2011106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of point and transect-based electrofishing to sample American eel (Anguilla rostrata) in wadeable riverine habitats

Abstract: -Dramatic declines in American eel (Anguilla rostrata) recruitment have resulted in strong conservation measures being implemented. Recovery actions in Ontario have included stocking of glass eels. Given the financial costs and imperative to undertake effective recovery actions, post-stocking monitoring is essential. In this study, pointand transect electrofishing sampling were compared in terms of eel detection, catch rates, size-selectivity, and power to detect changes in abundance. Transect sampling was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Eel may, for instance, be immobilized due to their length over the voltage gradient, reducing catchability (Zalewski and Cowx 1989), and stunned eel may be difficult to detect in water with low visibility (Koops 1980). However, data presented by Baldwin and Aprahamian (2012) showed relatively high ([ 0.6) catch efficiency of eel after one electrofishing run, indicating that eel occurrence and abundance may not be as difficult to estimate as commonly regarded (Reid 2011;Acou et al 2011).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Eel may, for instance, be immobilized due to their length over the voltage gradient, reducing catchability (Zalewski and Cowx 1989), and stunned eel may be difficult to detect in water with low visibility (Koops 1980). However, data presented by Baldwin and Aprahamian (2012) showed relatively high ([ 0.6) catch efficiency of eel after one electrofishing run, indicating that eel occurrence and abundance may not be as difficult to estimate as commonly regarded (Reid 2011;Acou et al 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Electrofishing is often carried out in wadeable small-to medium-sized running waters to monitor salmonid recruitment. Baldwin and Aprahamian (2012) stated that surveys focusing on salmonids also can potentially give good estimates of eel abundance, and Reid (2011) showed that transect-based sampling is better than point-based sampling of eel occurrence and abundance. However, it has also been argued that data on eel from such programmes are inadequate, with low precision in abundance estimates (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Small water bodies were fished completely, while larger ones were strip-sampled with comparable effort. EF was always performed by wading [30][31][32][33]. The sampling area of Kougri is located on the NakanbĂ© River to the east of Ouagadougou.…”
Section: Fish Sampling and Fish Determinationmentioning
confidence: 99%
“…Given the financial and human resources required, these surveys need to provide accurate and precise results and employ efficient sampling designs. To improve the design of electro fishing‐based inventories and monitoring, past research has addressed a diverse range of considerations including choice of sampling unit (Reid, ), sampling intensity (Stanfield, Lester, & Petreman, ), sampling effort (Jones & Stockwell, ; Tomanova, Tedesco, Roset, Berrebi Dit Thomas, & Belliard, ), number of electrofishing units (Kimmel & Argent, ), area of habitat sampled (Angermeier & Smogor, ; Simon & Morris, ), number of sampling sites (Smith & Jones, , ), and selection of sampling locations (Quist, Gerow, Bower, & Hubert, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thebackpackelectrofisherisacommonlyusedgeartosamplefishes from wadeable stream and river habitats (Rabeni, Lyons, Mercado-Silva,&Peterson,2009;Snyder,2003).Electrofishingsurveydataare used to assess biological integrity, monitor fish species that are of concerntomanagementorconservation,delineateareasofprotected habitat, assess the impacts of human activities, and describe the spatial-temporalpatternsofspeciesdiversityandcommunitycompositioninrelationtoenvironmentalfactors(e.g. Cao,Larsen,&Hughes, 2001;Reid&Hogg,2014).Giventhefinancialandhumanresources required,thesesurveysneedtoprovideaccurateandpreciseresults andemployefficientsamplingdesigns.Toimprovethedesignofelectro fishing-based inventories and monitoring, past research has addressedadiverserangeofconsiderationsincludingchoiceofsampling unit (Reid, 2011), sampling intensity (Stanfield, Lester, & Petreman, 2013),samplingeffort (Jones&Stockwell,1995;Tomanova,Tedesco, Roset,BerrebiDitThomas,&Belliard,2013),numberofelectrofishing units (Kimmel&Argent,2006),areaofhabitatsampled (Angermeier & Smogor, 1995;Simon & Morris, 2014), number of sampling sites (Smith & Jones, 2005, and selection of sampling locations (Quist,Gerow,Bower,&Hubert,2006).…”
Section: Introductionmentioning
confidence: 99%